Analisis Lemak dan Asam Lemak Jenuh pada Jagung Rebus di Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian Bogor - Utami, Maisari; Azizah Zelia Kusumo; Danuwarsa (Chemistry Department, Universitas Islam Indonesia, 2023)
Research on the testing of fat and saturated fatty acids of boiled corn has been carried out. This study aims to determine the quantity of fat and saturated fatty acids present in quantitatively analyzed boiled corn samples harvested from agricultural fields. The fat analysis was performed using the soxhlet extraction method, furthermore, the analysis of saturated fatty acids was performed using gas chromatography with Flame Ionization Detector (FID) as the detector. Based on the results of the test that has been carried out, the average fat content obtained using sohxlet extraction method from two different samples of corn which was repeated two times was 0,57%, this result were 0,58% from boiled corn samples I (simplo), 0,51% from boiled corn I (duplo), 0,60% boiled corn samples II (simplo), and 0,59% from boiled corn II (duplo). Furthermore, the total amount of saturated fatty acids obtained using the gas chromatography method was 20,43%, with the respective contents of 0.05% of myristic acid, 0.12% of lauric acid, and 20.26% of palmitic acid.